2017
DOI: 10.7759/cureus.1219
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Large Unruptured Fusiform Fenestrated Vertebrobasilar Junction Aneurysm

Abstract: Fenestrated vertebrobasilar junction aneurysms are rare vascular lesions. Microsurgical intervention is extremely difficult due to the complex anatomy in the vicinity of these aneurysms. Endovascular neurosurgery appears to be safe and should be considered as the first modality of treatment. This case study details the treatment of an unruptured fusiform fenestrated vertebrobasilar junction aneurysm with endovascular occlusion with stent-assisted coiling. The optimal angiographic exposure and selective microca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Our comprehensive literature research revealed that studies related with the topic are composed mostly of case reports. In the literature, a total of 113 BAF aneurysms of 101 patients had been treated endovascularly in 46 studies between 1993 and 2019 [4][5][6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Success rate of the treatment was reported as 97%, clinical success rate as 91%, and complication rate as 8.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Our comprehensive literature research revealed that studies related with the topic are composed mostly of case reports. In the literature, a total of 113 BAF aneurysms of 101 patients had been treated endovascularly in 46 studies between 1993 and 2019 [4][5][6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Success rate of the treatment was reported as 97%, clinical success rate as 91%, and complication rate as 8.8%.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 This combination of structural vessel wall abnormality and altered hemodynamics predisposes aneurysm development at the fenestrated vertebrobasilar junction. 2,4,6,10 The reported incidence of vertebrobasilar junction aneurysms is rare at approximately 0.33% of all intracranial aneurysms. 6 In the presence of a vertebrobasilar junction aneurysm, a high index of suspicion must be maintained due to the association with abnormal fenestration in up to 70% of cases, which can alter the treatment approach.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular intervention is preferred for these aneurysms. 3,4 We report 2 cases of fenestrated vertebrobasilar junction aneurysms successfully treated with different endovascular coiling techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The location of these aneurysms is proximal to the brainstem, and the wide varieties of the fenestrations complex and the presence of perforator vessels make the microsurgical approach extremely dificcult. 1,2,[8][9][10] An endovascular-based approach is becoming the first-line treatment, and meticulous preprocedural planning is extremely important to study the exact anatomy of the aneurysm-fenestration complex to determine the most appropriate endovascular therapeutic technique, Therefore, the three-dimensional rotational angiography (3DRA) is an extremely helpful tool to plan the endovascular treatment. 11 Kai et al proposed two types of classification.…”
Section: Palavras-chavementioning
confidence: 99%